'Faith in the system?' State‐funded faith schools in England and the contested parameters of community cohesion. Issue 2 (18th May 2012) - Dwyer, Claire; Parutis, Violetta
<x xml:space="preserve">Abstract</x> Within the wider context of interest in the relationships between faith and the state, this paper focuses on the case of state‐funded faith schools in England and how opposition to them has been mobilised and negotiated. Discussion focuses specifically on the role of community cohesion policy – a policy adopted to combat social and ethnic division after 2001 – and the contested parameters of this policy when introduced to monitor schools. Analysis suggests that faith school providers were able to interpret the policy in ways that challenged government articulations and reworked dominant meanings, revealing the political and spatial instabilities of the policy. However, our analysis suggests that these challenges to state meanings were less successful in shaping mechanisms to monitor admissions practices in faith schools – producing some unanticipated entanglements of state and religious authority with implications for the shaping of communal religious life. These findings both add to the wider critical policy analysis of community cohesion policy and contribute to debates about the role of religion in the public sphere.